Balimau Patang Tradition in Nagari Limau Lunggo Lembang Jaya Subdistrict, Solok Regency - Nurhayatil Nurhayatil (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
Balimau patang was an ancient tradition Centuries ago and still runs the people to this day. Balimau that is cleaned him self up with the afternoon croak that is balimau patang is about cleaning up in the afternoon. Balimau patang tradition is different from the common balimau tradition in Minangkabau people in usually. Balimau patang tradition no Whether it is lost in a river or other water but is done in the halls The village on the day before imposing the fast on the holy month of Ramadan with Bring lime and day dreams in a carano they gather In the form of a circle and carano was squeezed out in front of each other until the performance of the nagari children's art, after which a viciously volatile society or people that killed rezki filled their caranos with a variety of food or spare money, the tradition was that the baiang gathered around to forgive each other as in the sacred month of Ramadan